Re-definisi Superioritas Kulit Putih Terhadap Kulit Hitam Dalam Film The Help - Maulana Andinata Dalimunthe; Rizky Saputra (Avant Garde, 2021)
The Help movie becomes a site for redefining the superiority of white skin over black skin. The number of films with the central theme of oppression and discrimination against blacks makes whites feel they have to redefine their identity in the eyes of the world as people who bring enlightenment to blacks. The purpose of this paper is to identify forms of redefinition superiority in The Help movie. The theory that used in this paper is representation theory that formulated by Stuart Hall. The data obtained from observation of images (visual image) and sound/dialogue (audio) in which there is a text that describes the redefinition of the superiority of whites over blacks, and then analyzed using a constructionist approach. The results showed, The Help is an attempt to construct that not all whites discriminate against blacks, by presenting white figures who oppose discrimination and defend black rights through a book, which is then published and read by the public, but on the other hand, this film wants to convey that the black struggle not succeed without the presence of whites. Blacks will not get their freedom if whites do not take part in the struggle that they are doing. This film wants to redefine white superiority which does not always have a bad impact on black lives, because there are many positive aspects that can be generated through white superiority, such as improvement in the economic level, and raise black awareness of their potential.